Impact of Aqueous Ocimum gratissimum (Lyn) Leaf Extract on Growth Performance, Gut pH and Bacterial Counts in Broiler Chickens - Anugom, Y.O.; Ofongo , R.T.S. (International Journal of Poultry Science, 2019)
Background and Objectives: Phytobiotics are included in poultry diets as suitable alternatives to antibiotic growth promoters. Their impact on growth promotion and intestinal health as natural growth promoters also varies. This experiment was conducted to determine the impact of aqueous Ocimum gratissimum leaf extract on growth performance, gut pH and gut bacterial counts in broiler chickens. Materials and Method: One-hundred-day-old broiler chicks were randomly distributed into two treatment groups of fifty birds each with five replicates of ten birds per replicate. The control group was not administered aqueous O. gratissimum leaf extract, while the treatment group was administered aqueous O. gratissimum leaf extract. The experiment lasted six weeks and was arranged as a completely randomized design. Data on feed intake and weight gain were collected and the feed conversion ratio (FCR) was determined by calculation. The pH of the crop, proventriculus, ileum and caecum was measured and recorded and Escherichia coli (E. coli ) and Lactobacillus counts in these gut sections were determined. The data were subjected to one-way analysis of variance and significant differences were identified using Tukey’s post hoc test. Results: Aqueous O. gratissimum leaf extract significantly (p